Magnetoelectrical Transport Properties of La0.95Tb0.05MnO3 Perovskite Materials - Zhang, Kaituo; Zheng, Shu (Asian Journal of Chemistry, 2014)
Polycrystalline bulk perovskite La0.95Tb0.05MnO3 (LTMO) were synthesized by conventional solid-state reaction. Electric transport and magnetic and dielectric properties were examined. La0.95Tb0.05MnO3 exhibits semiconductor and its magnetic properties were spin-glass like behavior. It possesses the dielectric relaxation at lower 100 K. Furthermore, the dielectric properties remain almost unchanged at higher 100 K.